Immune activation and exhaustion marker expression on T-cell subsets in ART-treated adolescents and young adults with perinatal HIV-1 infection as correlates of viral persistence - Huang, Yuyang; Dhummakupt, Adit; Khetan, Priya; Nilles, Tricia; Zhou, Weiqiang; Mudvari, Prakriti; Szewczyk, Joseph; Chen, Ya Hui; Boritz, Eli; Ji, Hongkai; Agwu, Allison; Persaud, Deborah (Frontiers in Immunology, 2023)
HIV-1 infection in memory CD4+ T cells forms a latent reservoir that is a barrier to cure. Identification of immune biomarkers that correlate with HIV-1 reservoir size may aid with evaluating efficacy of HIV-1 eradication strategies, towards ART-free remission and cure. In adults living with non-perinatal HIV-1, the immune exhaustion marker PD-1 on central memory CD4+ T cells (Tcm) correlates with measures of HIV-1 reservoir size. Immune correlates of HIV-1 are less defined in adolescents and young adults with perinatal HIV-1. With multi-parameter flow cytometry, we examined immune activation (CD69, CD25, HLA-DR), and exhaustion (PD-1, TIGIT, TIM-3 and LAG-3) markers on CD4+ T cell subsets (naïve (Tn), central memory (Tcm), and the combination (Ttem) of transitional (Ttm) and effector memory (Tem) cells, in 10 adolescents and young adults living with perinatal HIV-1 (median age 15.9 years; median duration of virologic suppression 7.0 years), in whom HIV-1 reservoir size was measured with the Intact Proviral HIV-1 DNA Assay (IPDA) and an enhanced Tat/Rev limiting dilution assay (TILDA). RNA-seq was also performed on the unstimulated CD4 + T cells. The median total HIV-1 DNA concentration in memory CD4+ T cells was 211.90 copies per million CD4+ T cells. In the 7 participants with subtype B HIV-1 infection, the median intact proviral DNA load was 7.96 copies per million CD4+ T cells. Levels of HLA-DR and TIGIT on the Ttem were correlated with total HIV-1 DNA (r=0.76, p=0.015) and (r=0.72, p=0.023), respectively, but not with intact proviral load or induced reservoir size. HIV-1 DNA load was also positively correlated with transcriptional clusters associated with HLA-DR expression by RNA-seq. In contrast, PD-1 expression on Tcm was inversely correlated with total HIV-1 DNA (r=-0.67, p=0.039). Reservoir size by IPDA and TILDA were correlated (r=0.81, p=0.036). Thus, in this cohort of youths with long-standing treated perinatal infection, HLA-DR and TIGIT on Ttem were the key correlates of HIV-1 infected cell frequencies by total HIV-1 DNA, and not PD-1. Total HIV-1 DNA was negatively correlated with PD-1 expressing Tcm. These differences in longstanding perinatal HIV-1 infection compared with adult infection requires further study in larger cohorts.